Desenvolvimento de biofertilizante líquido produzido a partir de esterco bovino e cama de frango - Oliveira, Eduardo Rodrigo de (Universidade Federal de São Carlos, 2020)
The organic agriculture appeal for sustainability guides efforts towards the development and implementation of alternative techniques for the use of synthetic inputs in the fertilization of soils and crops. In this way, researchers and agricultural producers have been encouraged to experiment with biofertilizers made from the digestion of organic materials to replace mineral fertilizers. The difficulty lies in developing competitive alternatives in terms of production efficiency, besides the production costs and the range of attributes gained by the addition of synthetic inputs to fertilizers, such as plant growth hormone regulators. In this work, we developed an easy production method for a liquid biofertilizer made from the aerobic or anaerobic digestion of poultry litter and cattle manure and evaluated its nutrients composition and its fertilizer potential for plants. The developed liquid biofertilizer has contents of 450-600 mg L-¹ Nitrogen, 4-5 mg L-¹ Phosphorus, 560-650 mg L-¹ Potassium, in addition to the presence of Magnesium, Calcium, Boron, Iron, Zinc and Copper. It also demonstrate advantageous conditions for direct application without need of pH or salinity adjustment. In germination assessment with lettuce seeds of L. sativa, it was not toxic for dilutions of 5% to 50% and hindered the proliferation of bacteria and fungi. In the fluorescence spectroscopy analysis, the biofertilizer showed estimated concentrations of 11-26 µmol L-¹ of indolacetic acid (IAA), an important phytohormone responsible for plants root development. The optimum period of the biodigestion process was 30 to 45 days, the production and use of the biofertilizer is a promising alternative to replace mineral fertilizers, mainly those destined for vegetable crops.
Development of liquid biofertilizer produced from cattle manure and poultry litter
Desarrollo de biofertilizante líquido producido a partir de estiércol de ganado y arena para aves de corral
Keywords: Bioproduto; Resíduos orgânicos; Fertilidade agrícola; Sustentabilidade; Hormônio de crescimento; Bioproduct; Organic waste; Agricultural fertility; Sustainability; Growth hormone; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOQUIMICA DOS MICROORGANISMOS; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FERTILIDADE DO SOLO E ADUBACAO; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MICROBIOLOGIA E BIOQUIMICA DO SOLO